Impacto de la transformación digital para la creación de ventajas competitivas en empresas de servicio de transporte y almacenamiento de Lima Metropolitana - Lindao Flores, Manuel Alonso (2023)
In this research, we will explain and define different terms such as digital transformation, its elements and also the different competitive advantages that this change generates. The general objective of this research is to know the advantages obtained by transport and storage companies in Metropolitan Lima and the most important elements that are implemented. Digital transformation not only benefits companies, but also the whole society in which it takes place, as it develops the skills of citizens and allows for the creation of smart cities. The current pandemic has been an important factor for many to decide to carry it out or to have them in short term plans and not in the long term as it was before.This research has a quantitative approach, as variables will be quantified through the use of surveys applied to a sample and the results will be processed by means of statistical programmes such as Excel and SPSS. The results of the surveys will make it possible to achieve the objectives set out for this research and to check whether or not the hypotheses generated are fulfilled in reality. At the end of the research the results and their corresponding analysis will be presented, one of the main findings is that a large majority of respondents mentioned that digital transformation does have a positive impact on transport and warehousing companies in Metropolitan Lima.